2020
DOI: 10.31489/2020ch2/58-67
|View full text |Cite
|
Sign up to set email alerts
|

Features of sorption of rare-earth metals of cerium group by intergel systems based on polyacrylic acid, polymethacrylic acid and poly-4-vinylpyridine hydrogels

Abstract: Features of sorption of rare-earth metals of cerium group by intergel systems based on polyacrylic acid, polymethacrylic acid and poly-4-vinylpyridine hydrogelsThe work is devoted to study of sorption process of cerium and neodymium ions by individual hydrogels of polyacrylic acid (hPAA), polymethacrylic acid (hPMAA), poly-4-vinylpyridine (hP4VP) and intergel systems on their bases. Obtained results show that sorption properties (sorption degree, polymer chain binding degree, effective dynamic exchange capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Previous studies have shown that the intergel system should at least contain two components [45,46]. In the present study, the acidic and basic components of the system were PAA and P4VP hydrogels, respectively.…”
Section: Preparation Of the Intergel Systemmentioning
confidence: 66%
“…Previous studies have shown that the intergel system should at least contain two components [45,46]. In the present study, the acidic and basic components of the system were PAA and P4VP hydrogels, respectively.…”
Section: Preparation Of the Intergel Systemmentioning
confidence: 66%
“…Our earlier studies [2][3][4][5][6][7][8][9][10][11][12] showed that almost all intergel systems based on acidic (polyacrylic and polymethacrylic acids) and basic (poly-4-vinylpyridine and poly-2-methyl-5-vinylpyridine) rare-crosslinked polymer hydrogels exhibit higher activity than their constituents. Moreover, it was found that the ratio of polymers, at which a high sorption of ions is manifested, differ significantly depending on the nature of acidic and basic hydrogels and the nature of rare earth metals.…”
Section: Resultsmentioning
confidence: 99%
“…Method for the determination of lanthanum ions. Method for the determination of ions lanthanum in solution is based on the formation of a colored complex compound of the organic analytical reagent Arsenazo III with rare earth metal ions (REM); the concentration of lanthanum ions was calculated on a KFK-3M spectrophotometer at 650 nm [4][5][6][7][8]. The degree of extraction (sorption) was calculated using the formula:…”
Section: Experimental Partmentioning
confidence: 99%
“…, где m1вес сухого гидрогеля; m2вес набухшего гидрогеля [7][8][9][10][11][12]. РЕЗУЛЬТАТЫ И ОБСУЖДЕНИЕ Для интергелевой системы, составленной из сухих и набухших гидрогелей наблюдается дальнейшее увеличение электропроводности растворов по мере роста времени дистанционного взаимодействия.…”
Section: экспериментальная частьunclassified